Internet international marketing in the tourism industry : strategies for the survival of travel agents in Singapore - Zeng, Jared Qiyang (2010)
This paper recognizes the weakening power of the Singapore travel agents given the increasing penetration of the internet – where travel agents can be bypassed easily causing the shift in power to consumers. Thus, there is an increasing need for travel agents to strategize to retain and increase their consumer base. With that in mind, a survey and three-stage focus group were conducted to collect information, hence allowing us to derive segments (e.g. Value, Product, Brand Conscious segments), whom travel agents can choose to target. This paper will detail the travel process of the consumer based on their selection and enjoyableness criteria, and provide recommendations based on the extended marketing mix. The paper establishes criteria that different segments look for in their travel purchase, and these specific criteria is what travel agents should pay attention to when deciding who to target.